MDM2 Splice Variants and Their Therapeutic Implications - Harris, L. C. (Current Cancer Drug Targets, 2005)
MDM2 splice variants have now been identified in many different tumor types, and their expression has been associated with advanced disease. However, published data concerning their function is contradictory, and therefore their role in tumorigenesis and their potential as a therapeutic target are unclear. Expression of a specific splice variant, MDM2-B, in a transgenic mouse model results in tumor development; and expression of several splice variants has been shown to enhance tumor formation in Em-myc transgenic mice. However, expression of similar variants in vitro results in growth inhibition, an observation inconsistent with a transformed phenotype. The observed growth inhibition is p53-dependent, resulting from the binding of splice variants with an intact C-terminal RING finger domain to full-length MDM2 protein. In doing so, p53 can no longer bind MDM2, and p53 activity is elevated. Subsequent inactivation of p53 or p53-mediated apoptosis could contribute to the MDM2 splice variant-mediated tumorigenesis observed in vivo. However, MDM2 splice variants, like full-length MDM2, probably display p53-independent activities. Therefore, the potential for MDM2 splice variants as therapeutic targets will be dependent upon their phenotype within specific tumor types.
Keywords: oncogene